2019
DOI: 10.1002/nafm.10363
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Pest Management Tactic for Quagga Mussels: Site‐Specific Application of Fish Biological Control Agents

Abstract: The quagga mussel, Dreissena bugensis, is a harmful aquatic pest that invaded the Southwestern United States in 2007. Challenges with managing this pest have been encountered because the invaded systems are primarily open water sources used for human consumption and/or are connected to freshwater habitats containing threatened and endangered species. Existing chemical and physical control methods are undesirable, with use of some methods restricted or prohibited, because they pose risks to humans and ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Other studies have shown that different resident fishes can function as a natural biocontrol that manages different life stages of quagga mussels on different spatial scales in a site-specific manner (Culver et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that different resident fishes can function as a natural biocontrol that manages different life stages of quagga mussels on different spatial scales in a site-specific manner (Culver et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if any single fish species has potential to control invasive quagga numbers Lake Constance, roach seems to be the most promising candidate (Higgins & Vander Zanden, 2010; Pothoven & Fahnenstiel, 2013), as they are highly effective consumers, numerous and widely distributed in both basins (Alexander et al ., 2016). Other studies have shown that different resident fishes can function as a natural biocontrol that manages different life stages of quagga mussels on different spatial scales in a site‐specific manner (Culver et al ., 2021). Furthermore, it is known that cyprinids are able to crush indigestible hard components of their diet, like the valves of quaggas, and segregate them before ingestion (Sibbing, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Biological control agents that consume different stages of fouling organisms are being evaluated and show some promise for controlling particular species of concern (Culver et al. 2021 # [this special section], and unpublished data) and fouling communities as a whole (Atalah et al. 2014, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of examples exist where IPM has been proposed or trialled in aquatic systems, including invasive pest control in the environment, 99–101 for algae production 102 and for managing sea lice in salmon aqauculture 103 . Of direct relevance to bivalve aquaculture, Dumbauld et al 61 .…”
Section: Towards Ipm In Bivalve Aquaculturementioning
confidence: 99%